2020
DOI: 10.1177/1464420720942251
|View full text |Cite
|
Sign up to set email alerts
|

Contact behavior of functionally graded fractal surface

Abstract: Functionally graded surface has been a domain of research interest due to its use in various technologically advanced applications. The work focuses on static and dynamic analysis of rough fractal surface with exponentially graded material properties. The rough fractal surface is modeled in ANSYS with the coordinate points generated using the two variable modified Weierstrass–Mandelbrot function. Material gradation is applied to the rough surface model in such a way that, for any value of the gradation or inho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…It is interesting to note that the authors confirmed that the use of a suitable gradient of Young's modulus could overcome the contact damage occurring in several tribology applications. For example, one can avoid conical cracking in Hertzian indentation [14], improving the wear resistance [15]. Zhang et al [16] demonstrated that the gradient of Young's modulus, loading condition and the geometry of the FG structure have a direct impact on the crack propagation and shape in FGM coatings.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the authors confirmed that the use of a suitable gradient of Young's modulus could overcome the contact damage occurring in several tribology applications. For example, one can avoid conical cracking in Hertzian indentation [14], improving the wear resistance [15]. Zhang et al [16] demonstrated that the gradient of Young's modulus, loading condition and the geometry of the FG structure have a direct impact on the crack propagation and shape in FGM coatings.…”
Section: Introductionmentioning
confidence: 99%
“…From a microscopic point of view, the main models used to research rough surface contact problems are finite element models, statistical models, and fractal theory models. The finite element models use numerical algorithms to obtain directly the contact stress field on the rough surface and the relationship between the actual contact area and the normal contact load [4][5][6][7]. However, the elastoplastic character of contact between different materials or rough surfaces with larger sample length makes modeling challenging and increases computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Most works on functionally graded contact cover the indentation of flat functionally graded substrate or coating. Though an ample number of research have been carried out on functionally graded contact, only a few recent works [50][51][52][53] have taken roughness into consideration in the analyses. However, a detailed analysis of the graded fractal rough surface has not been attempted yet as per the best of the authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%